THE MANIFESTATION OF GENDER INEQUALITY IN THE GIVING OF DOWRY IN THE FORM OF WHITE CLOTH/SHROUD - Susi Susilawati; Adfiyanti Fadjar; Riri Anggriani; Hayyun Nur (Indonesia Media Law Review, 2026)
The article titled “The Manifestation of Gender Inequality in the Giving of Dowry in the Form of White Cloth/Shroud” is inspired by a social media story about a dowry consisting of a shroud and items associated with death. This incident occurred in Central Lombok, Nusa Tenggara Barat (NTB), specifically in Prapen. The news sparked lively discussions within the Ministry of Religious Affairs, particularly among heads of Religious Affairs Offices (KUA). While such an "unusual" or unconventional dowry may seem surprising, it has become a customary practice in Balaesang Tanjung, Donggala Regency, Central Sulawesi. In contrast to the traditional understanding of dowries, which serve as markers of marriage (distinguishing it from unlawful relationships), expressions of respect, appreciation, and protection for women, evidence of a man’s commitment to his future spouse, symbols of the woman’s accountability for the dowry received, and symbols of the man’s responsibility and consent, the practice of giving a shroud as dowry raises questions about its implications for gender equality. The study investigates how dowries consisting of white cloth/shrouds in Balaesang Tanjung manifest as gender inequality. The research employs an empirical approach, using primary data collected from community members, religious leaders, and prominent figures in Balaesang Tanjung, Donggala Regency. The methods include surveys, observations, interviews, and data collection for analysis and conclusions. The findings reveal that the practice of giving shrouds as dowries in Balaesang Tanjung reflects gender bias. This bias manifests in forms such as impoverishment or marginalization, stereotyping, subordination, violence, and the double burden experienced by women.